MYTHS AND REALITIES ABOUT CORONAVIRUS DISEASE–19 AMONG THE MEDICAL STUDENTS. - Palwasha Abbasi1 , Qamar Zaman Phul2 , Muhammad Ali Qureshi3 , Shagufta Memon4 , Mashal Siddiqui5 , Saba Bashir6 , Mehwish Kashif7 , Kashif Rasheed Shaikh8 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT Objective: To determine myths and realities about Coronavirus Disease–19 (COVID–19) among the Medical Students, Study Design: Cross sectional descriptive study. Place and Duration: Suleman Roshan Medical College, Tando Adam from January 2021 to September 2021. Methods: Myths and realities based questionnaire was designed as per WHO advisory recommendations for public myth buster. An online questionnaire-based information collection was adopted for various aspects of COVID-19 related information and level of awareness through What Apps and Google engine. A sample of 392 students qualified the study protocol. Data was entered in Microsoft Excel Sheet and analyzed in SPSS ver. 19.0 (P<0.05). Results: Mean age of participant’s 23.5±7.1 years. Male comprised 49.2% (n=193) compared to 50.7% (n=199) female participants (P=0.9). Most of response in Yes column was no specific drug is available for novel virus was noted as 269 (68.6%), in No column 251 (64.03%) was noted for COVID – 19 spreads by houseflies and largest frequency was for ‘holding breath for 10 sec indicates no COVID – 19 infection’ noted in 213 (53.3%). Overall, 70.1% student’s response was correctly yes. 98 (25%) participants responded thermal scanners can detect COVID – 19 virus, and 269 (68.6%) responded no specific drug is available to cure the COVID-19. Conclusion: We found both myths and realities of COVID – 19 from the Medical students. Public health department should provide more informative knowledge to overcome the havoc myths.